Creative Welded Metal Art: A Means to Financial Sustainability - Sobowale, Tolulope Oladimeji; Olarinde, Oladesu Johnson; Uzzi, Festus O.; Sunday, Omoniyi Samuel (NIU Journal of Humanities; Vol 5 No 1 (2020): KIU Journal of Humanities, Vol. 5 No. 1, March 2020, 2020)
Creative welded metal art is a global profession from the ancient to contemporary time. Exposure to working metal creatively in modern time started in Europe in 1930 and later spread to other parts of the world. This act, since its emergence in Nigeria has not being explored as it was the case with the traditional metal approach particularly among the academically trained artists (sculptors). This paper aimed at bringing to fore importance of formerly trained artist in the act of creative welded metal art (work) particularly as it regards utilitarian objects (such as chairs, console, curtain poles and tie-back etc). Data for the study was gathered from both primary and secondary sources. It was observed that creative welded metal art is highly accepted in the society and many academically trained sculptors are found wanting in the trade. Therefore, the paper concluded by encouraging art schools and their products in the act of creative welded metal art as a means to self-financial sustainability. Keywords: Creative, Metal, Welded, Economy, Self-Sustenance